A phylogenetic analysis and taxonomic revision of the oribatid mite family Malaconothridae (Acari: Oribatida), with new species of Tyrphonothrus and Malaconothrus from Australia - Colloff, Matthew J.; Cameron, Stephen L. (Zootaxa, 2013)
Hitherto, the Malaconothridae contained Malaconothrus Berlese, 1904 and Trimalaconothrus Berlese, 1916, defined by the possession of one pre-tarsal claw (monodactyly) or by three claws (tridactyly) respectively. However, monodactyly is a convergent apomorphy within the Oribatida and an unreliable character for a classification. Therefore we undertook a phylogenetic analysis of 102 species as the basis for a taxonomic review of the Malaconothridae. We identified two major clades, equivalent to the genera Tyrphonothrus Knülle, 1957 and Malaconothrus. These genera are redefined. Trimala-conothrus becomes the junior subjective synonym of Malaconothrus. Some 42 species of Trimalaconothrus are recom-bined to Malaconothrus and 15 species to Tyrphonothrus. Homonyms created by the recombinations are rectified. The replacement name M. hammerae nom. nov. is proposed for M. angulatus Hammer, 1958, the junior homonym of M. an-gulatus (Willmann, 1931) and the replacement name M. luxtoni nom. nov. is proposed for M. scutatus Luxton, 1987, the junior homonym of M. scutatus Mihelčič, 1959. Trimalaconothrus iteratus Subías, 2004 is an unnecessary replacement name and is a junior objective synonym of Malaconothrus longirostrum (Hammer 1966). Malaconothrus praeoccupatus Subías, 2004 is a junior objective synonym of M. machadoi Balogh & Mahunka, 1969. Malaconothrus obsessus (Subías, 2004), an unnecessary replacement name for Trimalaconothrus albulus Hammer 1966 sensu Tseng 1982, becomes an available name for what is in fact a previously-undescribed species of Malaconothrus. We describe four new species of Tyrphonothrus: T. gnammaensis sp. nov. from Western Australia, T. gringai sp. nov. and T. maritimus sp. nov. from New South Wales, and T. taylori sp. nov. from Queensland. We describe six new species of Malaconothrus: M. beecroftensis sp. nov., M. darwini sp. nov. M. gundungurra sp. nov. and M. knuellei sp. nov. from New South Wales, M. jowettae sp. nov. from Norfolk Island, and M. talaitae sp. nov. from Victoria.